Uterine torsion in pregnancy, expect the unexpected: case report - Mokhtar, Huda Nabihah; Faridz, Sumayyah Mohammed; Ismail, Rohana; Yaacob, Nasuha; Ramli, Roziana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Uterine torsion in pregnancy is a rare condition, but potentially life-threatening. The non-specific clinical features make preoperative diagnosis difficult and most cases are discovered during caesarean deliveries done for other obstetric indications. Authors present 2 cases of uterine torsion with different clinical presentation and outcome. Case 1 was a G3P2 at 36 weeks with twin pregnancy presented in active labour with a prolapsed cord. A 180 degrees uterine torsion was discovered only after delivery of the foetuses, resulting in inadvertent posterior uterine wall incision. Case 2 was a G6P5 at 35 weeks who presented with an acute abdomen and went into shock. At laparotomy, a 360 degrees uterine torsion was discovered complicated with placental abruption, causing a fresh stillborn baby. These cases highlight uterine torsion as a rare but important diagnosis in obstetrics, which could be associated with potentially devastating outcome.